2008
DOI: 10.1163/156856807782753877
|View full text |Cite
|
Sign up to set email alerts
|

Statistical regularities of art images and natural scenes: Spectra, sparseness and nonlinearities

Abstract: Paintings are the product of a process that begins with ordinary vision in the natural world and ends with manipulation of pigments on canvas. Because artists must produce images that can be seen by a visual system that is thought to take advantage of statistical regularities in natural scenes, artists are likely to replicate many of these regularities in their painted art. We have tested this notion by computing basic statistical properties and modeled cell response properties for a large set of digitized pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
125
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 39 publications
8
125
1
Order By: Relevance
“…This type of research is in line with the notion that aesthetic artworks share specific and universal properties, which reflect functions of the human visual system in particular and of the human brain in general [Zeki 1999;Reber et al 2004;Redies 2007]. Over the years, different research groups proposed several properties that characterize aesthetic paintings [Birkhoff 1933;Arnheim 1954;Berlyne 1974;Graham and Field 2007;Redies et al 2007;Rigau et al 2008;Forsythe et al 2011]. For example, Redies et al [Redies et al 2007] and Graham and Field [Graham and Field 2007] have shown that, on average, log-log plots of the radially averaged 1d power spectrum of greyscale images tend to drop according to a power law, similar to results that have been described for natural scenes [Field et al 1987;Burton and Moorhead 1987].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…This type of research is in line with the notion that aesthetic artworks share specific and universal properties, which reflect functions of the human visual system in particular and of the human brain in general [Zeki 1999;Reber et al 2004;Redies 2007]. Over the years, different research groups proposed several properties that characterize aesthetic paintings [Birkhoff 1933;Arnheim 1954;Berlyne 1974;Graham and Field 2007;Redies et al 2007;Rigau et al 2008;Forsythe et al 2011]. For example, Redies et al [Redies et al 2007] and Graham and Field [Graham and Field 2007] have shown that, on average, log-log plots of the radially averaged 1d power spectrum of greyscale images tend to drop according to a power law, similar to results that have been described for natural scenes [Field et al 1987;Burton and Moorhead 1987].…”
Section: Introductionsupporting
confidence: 62%
“…Over the years, different research groups proposed several properties that characterize aesthetic paintings [Birkhoff 1933;Arnheim 1954;Berlyne 1974;Graham and Field 2007;Redies et al 2007;Rigau et al 2008;Forsythe et al 2011]. For example, Redies et al [Redies et al 2007] and Graham and Field [Graham and Field 2007] have shown that, on average, log-log plots of the radially averaged 1d power spectrum of greyscale images tend to drop according to a power law, similar to results that have been described for natural scenes [Field et al 1987;Burton and Moorhead 1987]. This finding indicates that images of artworks and natural scenes share a scale-invariant (fractal-like) power spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…An analogous scale- :4 invariance was found in the grayscale surfaces for a wide range of art images 9,10,18 , in parallel to what is a known characteristic of natural scenes [19][20][21] . Natural images tend to have characteristic frequency spectra in which amplitude falls proportionally with increasing frequency and thus on average varies roughly as f -1 [or with a slope of -1 for log amplitude versus log frequency plot 22 .…”
Section: Introductionsupporting
confidence: 60%
“…The finding that artworks, which might appear superficially unstructured, contain a measurable degree of regularity was surprising. Building on this initial analysis, a number of groups have extended the range of fractal analysis techniques to quantify the visual complexity of a wide range of art images [6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…u = f cos θ and v = f sin θ , and construct S( f , θ ). A number of studies have demonstrated ( [15], [16], [17]) that, by using polar coordinates and summing up the power spectra S over all directions θ , most natural images show a power distribution S( f ) which can be approximated by…”
Section: A Local Power Spectrum Slopementioning
confidence: 99%